EKSPERIMENTASI MODEL PEMBELAJARAN THINK-PAIR-SHARE (TPS), THINK-TALK-WRITE (TTW) DAN TWO STAY-STRAY (TSTS) PADA MATERI BANGUN RUANG SISI DATAR DITINJAU DARI SELF-EFFICACY - Viqriah, Khafittulloh; Budiyono, Budiyono; Subanti, Sri (Journal of Mathematics and Mathematics Education, 2015)
Abstract: The aims of this research was to determine the effect of learning models on mathematics achievements and learning interest viewed from students self-efficacy. The learning model compared were TPS, TTW, and TSTS. The type of the research was a quasi-experimental research. The population were all of the students in grade 8th of Junior High School in Sleman regency. Sampling was done by stratified cluster random sampling. The samples were students of SMPN 1 Kalasan, SMPN 4 Kalasan, and SMPN 2 Ngemplak. The instruments used were mathematics achievement tests and self-efficacy questionnaire. The data was analyzed by using unbalanced two-ways Anova. The conclusions were as follows. (1) TPS gives better mathematics achievement than TTW, and both gives better mathematics achievement than TSTS. (2) Students who have high and medium self-efficacy have the same mathematics achievement, students who have medium and low self-efficacy have the same mathematics achievement, students who have high self-efficacy was better than students who have low self-efficacy. (3) For TPS and TTW, students who have high, medium, and low self-efficacy have the same mathematics achievement. For TSTS, students who have high and medium self-efficacy have the same mathematics achievement, students who have medium and low self-efficacy have the same mathematics achievement, students who have high self-efficacy was better than students who have low self-efficacy. (4) For students who have high and medium self-efficacy, TPS,TTW, andÂ  TSTS gives the same mathematics achievement. For students who have low self-efficacy, TPS andÂ  TTW gives the same mathematics achievement, TPS gives better mathematics achievement than TSTS, and TTW gives better mathematics achievement than TSTS .Keywords: Think-Pair-Share (TPS), Think-Talk-Write (TTW), Two Stay-Two Stray (TSTS), self-efficacy